Bond market development in Cambodia - Norng Ratana; Kouwenberg, Roy; Tang, John C.S.; Dimmitt, Nicholas J.; French Government; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2006)
In ASEAN, the majority of the member-countries has their own financial market and is in the process of furthering the development of those markets. Even though those markets are not as efficient as the markets in developed countries, it helps to facilitate the flow of funds within the country better than before. Recently in Cambodia, both private and public sector in Cambodia are in need of funds. In addition, Cambodia joined ASEAN and WTO. This would require the country to have a more developed financial system to facilitate the global trade and transaction across the partner countries. Government has set a financial sector blueprint for 2001-2010, which is used as the road map to develop bond market. This research study aimed to learn from the experience about bond market development in other countries in Asia, to find out the obstacle and the point they figured out in developing their local bond market. Also combined with the study on the current financial sector in Cambodia, the author will mentioned the issues and constraints remains for Cambodia to do some further development. The recommendation will he provided the suggestion to develop each weak area
a research study submitted in partial fulfillment of the requirements for the degree of Master of Business Administration
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 2006
Keywords: Bond market -- Cambodia